The Rosaceae Genome Database: A Tool for Improving Apricot Genetics and Culture - Abbot, Albert Glenn; Zebentenvayeva, T.; Georgi, L.; Garay, L.; Horn, R.; Jung, S.; Main, D.; Lalli, D. A.; Decroocq, V.; Badenes, María L.; Baird, W. V.; Reighard, G. L. (ISHS, 2022)
The importance of high-quality fruit and the intrinsic difficulties of breeding in a perennial species require the development and application of structural and functional genomic databases for the sustained improvement of Rosaceaous fruit crops. Identification and characterisation of genes controlling the genetic basis of the traits, and their tagging with molecular markers, permits facilitated introgression of important characters, speeding development of new breeding material combining the best traits formerly isolated in separate varieties. Currently, there are two major bottlenecks to the identification, characterisation and direct manipulation of genes important to Rosaceae crop cultivation. These are the lack of a candidate gene database and a genetic/physical map resource in which to search for the genes. In co-operation with other researchers world-wide, we are developing such databases for peach as a genome index species for the Rosaceae. The work towards this Rosaceae genome database is presented here in order to update Rosaceae community researchers on the progress of this database and its application to problems in apricot breeding and sustainability.